ANALISIS RESPON PEDAGANG USAHA KECIL PADA PEMBIAYAAN DI BANK SYARIAH(Studi Kasus: Pedagang Usaha Kecil Kampung Lundar) - Selvia Selvia; Sandra Dewi (Jurnal Salome : Multidisipliner Keilmuan, 2024)
The background of this study is to analyze the response of small business traders to financing in Islamic banks with a case study of small business traders in Lundar village. Islamic financing is considered an attractive alternative for small business traders because of the profit-sharing and usury-free principles it offers. This study uses a qualitative descriptive approach with an interview method involving 60 small business trader informants. Data were collected through direct interviews with Lundar market traders and analyzed using observation, interview, and documentation methods. The results of the study show that the majority of small business traders in Lundar village have a positive response to the financing offered by Islamic banks. Most informants are satisfied with Islamic financing products that are considered appropriate to their business capital needs. The positive impact of this financing can be seen from the increase in turnover and business profits as well as the ability of traders to expand their businesses and improve product quality. However, this study also found several challenges faced by traders in accessing Islamic financing, including the administrative process which is considered still long and the amount of financing that sometimes does not meet capital needs. This study suggests that Islamic banks improve their services by providing better education to small business traders regarding Islamic financial products, and continue to innovate in providing flexible financing schemes that suit the needs of traders. Thus, Islamic financing can contribute more significantly to the development of small businesses in Lundar village.